(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Management of infections in the maxillofacial region is one of the most challenging situation that a maxillofacial surgeon faces. Early recognition of such infections and the decision making for the right choice of treatment is of prime importance. In this article, a case of canine space infection extending to involve the medial canthus of the eye and the periorbital region due to an odontogenic cause is presented with emphasis on aesthetic consideration while planning incision and drainage in the facial area.